A novel intestinal diagnosis system based on inchworm-like micro robot with wireless power transfer. Issue 1 (June 2021) - Han, Ding; Yan, Guozheng; Wang, Zhiwu; Jiang, Pingping
Abstract: A novel intestinal diagnosis system based on inchworm-like micro robot with wireless power transfer have been proposed in this study. The micro robot has been minimized in size to Φ 14mm in diameter, like a capsule. It can be swallowed in without pain. Furthermore, the expanding mechanism and telescoping mechanism make it possible to possess bidirectional motion and stable anchorage. Powered by wireless power transfer system, though receiving coil is embedded in a limited space, it also supplies enough power 653mW for micro robot system after optimization. In addition, wireless communication and human machine interface system is used to capture the video image in intestine. At last, some in vitro experiments are conducted with prototype in a porcine intestine. Under the optimized wireless power transfer system, with transmission efficiency 4.66%, the communication error rate at 1m distance is just 0.7%. The speed of micro robot in the viscoelastic and slippery intestine could reach 4.38 cm/min. And operators can obtain images inside the intestine by the human machine interface system in real time. All of the above show a good performance of the proposed intestinal diagnosis system based on inchworm-like micro robot with wireless power transfer.